(3QSGdI GdOGeZGfi aj GdYbGFOs - (3CHh YHO Gddg eMeO Hf Ydj,J (B478 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi effg HGdcdjI hGdLRFjI hHYO aEfc (B_ (3CjgG GdCN GdeMH SCdJfi ai ENJdGa GdCeI ai GdYbGFO hCdReJfi Cf dG BdhG LgOkG ai HjGf eG CdJeSc Hg CHdZ GdhSGFd s
(3BNQgG (B:s
(3hGYde Cfi eG JdceJ dg HeG JcdeJ Edi hbO NHQJ LejY Cgd GdePGgH hdeG VQHJ ai GdYdhe hGQJMdJ dgG ef CcKQ GdCbWGQ hNHQJ LejY ePGgH GdESdGe hWQGFbge hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3Ydi ZGTjJgG eWGdYI deMeO Hf GdMSjf Hf GdMSf Hf CejQ GdeDefjf cJHJ deMeO Hf YHO Gddg Hf GdgGOis
(3Ydi WQJgG eWGdYI CjVkG dYGed Hf YHO Gddg Hf YGeQ Hf Ydis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B276s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs